Simulation Analysis of Orthotropic Anisotropic C/SiC for Automotive Ventilated Brakes - Zhu Yuling; Wang Youqiang; Zhao Tao; Li Mengjie; He Yan (Jixie chuandong)
Using the theory related to thermal coupling and heat transfer, the finite element software Abaqus is used to establish an orthogonal anisotropic C/SiC model of an automotive ventilated brake disc. Based on this model, different braking initial velocities, different braking pressures and different longitudinal expansion coefficients of the brake disc during emergency braking are simulated and analyzed. The results show that the temperature profile of the nodal unit of the brake disc exhibited "sawtooth" fluctuations under the effect of thermal coupling, and the thermal stresses mainly appeared in the middle region of the friction contact. The higher the braking pressure and initial speed during emergency braking are, the higher the temperature rise of the disc surface will be. However, the effect of different disc expansion coefficients on the maximum disc temperature is not significant.